Selective adsorption of sulfur dioxide in a robust metal-organic framework material - Savage, Mathew; Cheng, Yongqiang; Easun, Timothy L.; Eyley, Jennifer E.; Argent, Stephen P.; Warren, Mark R.; Lewis, William; Murray, Claire; Tang, Chiu C.; Frogley, Mark D.; Cinque, Gianfelice; Sun, Junliang; et al. (Wiley, 2016)
Selective adsorption of SO2 is realized in a porous metal–organic framework material, and in-depth structural and spectroscopic investigations using X-rays, infrared, and neutrons define the underlying interactions that cause SO2 to bind more strongly than CO2 and N2.